A Study on the Insight Development according to Phrarajpariyattayakorn’s Teaching (Boonraung Sārado) - Ñāṇasiddhi (Siriwang), Phramaha Nitithat; Vuddhikaro, Phramaha Somboon; Raksachom, Kritsana (Mahachula Academic Journal, 2023)
This thesis entitled ‘A Study on the Insight Development according to Phrarajpariyattyakorn’s (Boonrueang Sãrado)’ has three objectives: (1) to study the insight development according to Buddhist scriptures, (2) to study the teachings and practical guidelines of Phrarajpariyattyakorn’s Teaching (Boonrueang Sãrado), and (3) to study the practical result gained from the insight development according to Phrarajpariyattyakorn’s Teaching (Boonrueang Sãrado). This research employed the qualitative research methodology by studying documents and interview of 15 Key informants. The research results showed that according to the Buddhist scriptures the insight development basically means the practices in accordance with four foundations of mindfulness: (1) Kãyãnupassanã, (2) Vedanãnupassanã, (3) Cittãnupassanã, and (4) Dhammãnupassanã; while practicing one contemplates on the following objects of insight development: five kinds of khandha, twelve kinds of Ãyatana, Eighteen kinds of Dhãtu, twenty-two kinds of Indriya, four types of Ariyasacca, and twelve kinds of Paµiccasamuppãda. It is said that Phrarajpariyattyakorn (Boonrueang Sãrado) taught the insight development according to four foundations of mindfulness whereby practitioners are inculcated to be mindful on the mind-moment through contemplating on Rũpa, Nãma, Kãya, Citta and Dhamma till the arising of dissatisfactoriness and non-lustfulness. As a result, they come to have insightfulness through three common characteristics, Aniccatã, Dukkhatã and Anattatã whereby detachment is completely actualized. Through the mentioned practical methods, practitioners realize the bodily, mental, ethical and wisdom changes leading them to have the real comprehension of Buddhism and themselves where they can control their emotions in both pleasant (Iṭṭhãrammaṇa) and unpleasant (Aniṭṭhãrammaṇa) and thereby applying them to daily life and living happily in a society.